Effect of the Affordable Care Act on healthcare utilization for Veterans with spinal cord injuries and disorders. (4th July 2022) - Martinez, Rachael N.; Smith, Bridget M.; French, Dustin D.; Hogan, Timothy P.; Gonzalez, Beverly; Osteen, Chad M.; Hatch, Maya; Anderson, Vicki; Tarlov, Elizabeth; Silva, Abigail; Goldstein, Barry; Stroupe, Kevin T.
Abstract : Context/Objective: Provisions of the Affordable Care Act (ACA) potentially increase insurance options for Veterans with disabilities. We examined Veterans with spinal cord injuries and disorders (SCI/D) to assess whether the ACA was associated with changes in healthcare utilization from Department of Veterans Affairs (VA) healthcare facilities. Design: Using national VA data, we investigated impacts on VA healthcare utilization pre- (2012/13) and post-ACA (2014/15) implementation with negative binomial regression models. Setting: VA healthcare facilities. Participants: 8, 591 VA users with SCI/D. Veterans with acute myelitis, Guillain-Barré syndrome, multiple sclerosis, or amyotrophic lateral sclerosis were excluded as were patients who died during the study period. Interventions: We assessed VA healthcare utilization before and after ACA implementation. Outcome Measures: Total numbers of VA visits for SCI/D care, diagnostic care, primary care, specialty care, and mental health care, and VA admissions. Results: The number of VA admissions was 7% higher in the post than pre-ACA implementation period (P < 0.01). The number of VA visits post-implementation increased for SCI/D care (8%; P < 0.01) and specialty care (12%; P < 0.001). Conversely, the number of mental health visits was 17% lower in the post-ACA period (P < 0.001). Veterans with SCI/D who live <5 miles from their nearest VA facility received VA care more frequently than those ≥40 miles from VA (P < 0.001). Conclusion: Counter to expectations, results suggest that Veterans with SCI/D sought more frequent VA care after ACA implementation, indicating Veterans with SCI/D continue to utilize the lifelong, comprehensive care provided at VA.